SEMANTIC PROFILE OF UNIVERSITYâ€™S VISION AND MISSION: A PROSPECTIVE CASE STUDY - Tawami, Tatan (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2021)
This paper proposes the semantics of product functions in a private university in Indonesia. The so-called product of the university is the Vision and Mission that carries intended and aligned message to its target readers/customers. Therefore, this research aims at mapping the semantic profile of Universityâ€™s Vision and Mission. Analysing this issue, qualitative-descriptive method was implemented to break-down the message of the product function. The results showed that the product clusters the message into general structure of the product, open word class clustering, and word clustering based on meaning association. The semantics then voluntarily specifies particular strategies based on its meaning association. Additionally, the findings suggested that the product function was discovered by analysing the descriptive words in the Vision and Missions. From this discovery, the product can then be mapped into its function class and type. This then specifies possible strategies implemented in â€œmarketingâ€ the product. From the result, it can be concluded that mapping out the message and strategy of the product can best aid universities in improving their language design in every product they have.